Research on the fluctuation of reticulocyte during different altitude training patterns in swimming athletes - Yang, X.; Liu, Y.; Qu, C. (Exercise Biochemistry Review, 2018)
Objective To explore the fluctuation of reticulocyte during different altitude training in swimming athletes and their difference between altitude training focused on special aerobic capacity and altitude training focused on high load and sprint, to provide the theory basis for further analyze the altitude training improve the physiological function and athletic performance.